2019
DOI: 10.3390/brainsci9010012
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem Group: Useful Intervention for Inpatients with Anorexia Nervosa?

Abstract: Low self-esteem is a common feature in Anorexia Nervosa (AN) and has been hypothesised to act as a predisposing, precipitating, and perpetuating factor. The aim of this study was to assess the effectiveness of a Cognitive Behavioural Therapy (CBT)-based self-esteem group in a naturalistic setting of patients with AN in an inpatient treatment programme. Included in this study were 119 female patients diagnosed with AN, with all participants completing self-report questionnaires before and after the intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
(40 reference statements)
2
10
0
1
Order By: Relevance
“…Effect sizes suggest the self-esteem group therapy was beneficial for addressing low self-esteem. Furthermore, the magnitude of the effect sizes on the RSE (Cohen’s D = 0.21) are comparable to previous studies that have reported effect sizes on the same measure following self-esteem intervention (Cohen’s D = 0.13–0.39) [ 27 , 28 ]. The Treatment as Usual programme at Newbridge House has been rated independently by the UK government’s Care Quality Commission as “Outstanding” [ 45 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Effect sizes suggest the self-esteem group therapy was beneficial for addressing low self-esteem. Furthermore, the magnitude of the effect sizes on the RSE (Cohen’s D = 0.21) are comparable to previous studies that have reported effect sizes on the same measure following self-esteem intervention (Cohen’s D = 0.13–0.39) [ 27 , 28 ]. The Treatment as Usual programme at Newbridge House has been rated independently by the UK government’s Care Quality Commission as “Outstanding” [ 45 ].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, Newns et al, [ 23 ] found that a long-term intervention over the course of 20 months led to improved self-esteem in eating disordered (though not exclusively AN) participants. Further evidence for a brief, CBT-based self-esteem group therapy comes from Adamson, Ozenc, Baille and Tchanturia, [ 28 ] who found that a six-week group led to significant improvements in self-esteem and a small improvement in self-perceived ability to change in women with AN in an inpatient setting. These findings identify that a group-based approach to improving low self-esteem in adult populations is effective and further research is required exploring this in an adolescent population.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…Self-esteem may be increased through interventions (for a meta-analysis, see O'Mara, Marsh, Craven, & Debus, 2006). Effects from these selfesteem interventions generalize to other areas of psychological functioning (e.g., Adamson, Ozenc, Baillie, & Tchanturia, 2019). Thus, including elements that target self-esteem in interventions for perfectionism (for a metaanalysis, see Suh, Sohn, Kim, & Lee, 2019) appears worthwhile.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The persistence of low levels of self-esteem and satisfaction due to an excessive importance devoted to weight and body size is a diagnostic criterion both for DSM-5 AN and BN categories. Low self-esteem has been hypothesized to be a risk factor as well as a predisposing, precipitating, and maintaining mechanism of AN (Adamson, 2019), with a number of negative effects on intimate/interpersonal relationships (Miniati et al, 2018). Self-esteem maintains eating disorder psychopathology, especially contributing to concerns around shape, weight, and dietary restraint (Fairburn et al, 2003).…”
Section: Domain 'Self-esteem and Satisfaction'mentioning
confidence: 99%